ANALISIS STRUKTUR TEKS, KOGNISI SOSIAL, DAN DIMENSI SOSIAL DALAM NOVEL PULANG KARYA TERE LIYE (ANALYSIS OF TEXT STRUCTURE, SOCIAL COGNITION, AND SOCIAL DIMENSIONS IN NOVEL PULANG CREATION TERE LIYE) - Ahmad Jamaludin (Universitas Lambung Mangkurat, 2022)
AbstractAnalysis of Text Structure, Social Cognition, and Social Dimensions in Novel PulangCreation Tere Liye. The purpose of this study is to describe the structure of the text, socialcognition, and dimensions used in the novel Pulang by Tere Liye when viewed from theanalysis of Teun A. Van Dijk's critical discourse analysis. This study uses the CriticalDiscourse Analysis approach developed by Teun A. Van Dijk and uses the descriptivequalitative method. The results obtained in the novel Pulang Tere Liye's text structure isdivided into several elements, namely, macrostructure, superstructure, and microstructure.The author's macro structure has the theme of betrayal. There are several stages in thesuperstructure, namely the stages of settlement, conflict arising, increasing conflict, climax,and resolution. Microstructure uses semantics, syntax, stylistic, and rhetoric. Semanticelements are divided into several parts, namely, background, detail and purpose. The settingof this novel are Sumatra, the Jungle Forest of Sumatra, Hong Kong, Tokyo Airport, theCapital Harbor. The details used by the author are more beneficial to him but some aredetrimental to him. The author's intent is stated explicitly and clearly so that the readerunderstands and easily understands the story. In syntax, it is divided into several parts,namely coherence, pronouns, and sentence forms. Coherence used is meaningful coherenceof cause and effect, emphasis, location or time, addition, inference, and conflict. Thepronouns used in this novel are the first singular pronouns aku (I), the first plural pronounkami and kita (we), the second singular pronoun, anda, kau and mu, (you), the second pluralpronoun kalian (all of you), the third singular pronoun ia and dia, and the third pluralpronoun mereka (they, them).The froms of sentences used by the writer are active andpassive sentences. The style of language used is the style of language anaphora, epanalepsis,asonance, simile, pleonasm, correction, aptronym, antithesis, sarcasm, alonym, erotesis, andasidenton. Rhetorical cases are divided into several parts, namely graphics; the author usesemphasis with words or sentences in italics. The metaphors used by the writer are dailyexpressions, proverbs, and proverbs. The expressions used referred to sad and happyexpressions. The social cognition is divided into several elements, namely knowledge,opinions and attitudes, and ideology. Furthermore, the social dimension is divided intoseveral elements, namely power and access.Key words: critical discourse, text structure, social cognition, social dimensions, novelAbstrakAnalisis Struktur Teks, Kognisi Sosial, dan Dimensi Sosial dalam Novel Pulang KaryaTere Liye. Tujuan penelitian mendeskripsikan struktur teks, kognisi sosial, dan dimensiyang digunakan dalam novel Pulang karya Tere Liye bila ditinjau dari analisis wacana kritisTeun A. Van Dijk. Penelitian ini menggunakan pendekatan Analisis Wacana Kritis yangdikembangkan oleh Teun A. Van Dijk dan menggunakan metode deskriptif kualitatif. Hasilpenelitian yang diperoleh dalam novel Pulang karya Tere Liye yaitu struktur teks terbagimenjadi beberapa elemen yaitu struktur makro, superstruktur, dan struktur mikro. Strukturmakro pengarang mengangkat tema penghianatan. Superstruktur terdapat beberapa tahapanyakni tahap penyituasian, tahap pemunculan konflik, tahap peningkatan konflik, tahapklimaks, dan tahap penyelesaian. Struktur mikro menggunakan semantik, sintaksis, stilistik,dan retoris. Elemen semantik terbagi beberapa bagian yaitu latar, detil dan maksud. Lataryang digunakan dalam novel ini yaitu di Sumatera, Hutan Rimba Sumatera, Hongkong,Bandara Tokyo, Pelabuhan Ibu Kota. Detil yang digunakan pengarang lebih menguntungkandirinya namun ada pula yang merugikan dirinya. Maksud disampaikan penulis secaraeksplisit dan jelas sehingga pembaca mengerti dan mudah memahami cerita. Pada sintaksis,terbagi menjadi beberapa bagian yaitu koherensi, kata ganti, dan bentuk kalimat. Koherensiyang digunakan yaitu koherensi bermakna sebab akibat, penekanan, lokasi atau waktu,penambahan, penyimpulan, dan pertentangan. Kata ganti yang digunakan yaitu kata gantipertama tunggal aku, kata ganti pertama jamak kami dan kita, kata ganti kedua tunggal anda,kau, dan mu, kata ganti kedua jamak kalian, kata ganti ketiga tunggal ia dan dia, kata gantiketiga jamak mereka. Bentuk kalimat yang digunakan penulis yaitu kalimat aktif dan pasif.Gaya bahasa yang digunakan yaitu gaya bahasa anafora, epanalepsis, asonansi, simile,pleonasme, koreksio, aptronim, antitesis, sarkasme, alonim, erotesis, dan asidenton. Retoristerbagi menjadi beberapa bagian yaitu grafis, penulis menggunakan penekanan dengan kataatau kalimat yang dicetak miring. Metafora yang digunakan penulis yaitu ungkapan seharihari, peribahasa, dan pepatah. Ekspresi yang digunakan yaitu ekspresi sedih dan bahagia.Pada kognisi sosial terbagi menjadi beberapa elemen yaitu pengetahuan, opini dan sikap,serta ideologi. Selanjutnya, dimensi sosial terbagi menjadi beberapa elemen yaitu kekuasaandan akses.Kata-kata kunci: wacana kritis, struktur teks, kognisi sosial, dimensi sosial, novel